1992
DOI: 10.1101/gad.6.9.1728
|View full text |Cite
|
Sign up to set email alerts
|

The dorsal gradient morphogen regulates stripes of rhomboid expression in the presumptive neuroectoderm of the Drosophila embryo.

Abstract: rhomboid (rho) encodes a putative transmembrane receptor that is required for the differentiation of the ventral epidermis. It is initially expressed before the completion of cellularization in lateral stripes within the presumptive neuroectoderm. Here, we present evidence that the maternal morphogen dorsal (dl) acts in concert with basic helix-loop-helix (b-HLH) proteins, possibly including twist (twi), to activate rho in both lateral and ventral regions. Expression is blocked in ventral regions (the presumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
321
1
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(338 citation statements)
references
References 51 publications
14
321
1
2
Order By: Relevance
“…TWIST1 represses E-cadherin, which results in the activation of mesenchymal markers and cell motility suggesting that TWIST1 promotes epithelial-to-mesenchymal transition. TWIST1 may also regulate the expression of the bHLH repressor SNAIL that acts as a boundary repressor by downregulating the expression of ectodermal genes within the mesoderm (Ip et al, 1992). The HIF pathway can also regulate E-Cadherin repression, presumably via SNAIL (Esteban et al, 2006).…”
Section: Twist1 Is a Target Of Hif-2a Eh Gort Et Almentioning
confidence: 99%
“…TWIST1 represses E-cadherin, which results in the activation of mesenchymal markers and cell motility suggesting that TWIST1 promotes epithelial-to-mesenchymal transition. TWIST1 may also regulate the expression of the bHLH repressor SNAIL that acts as a boundary repressor by downregulating the expression of ectodermal genes within the mesoderm (Ip et al, 1992). The HIF pathway can also regulate E-Cadherin repression, presumably via SNAIL (Esteban et al, 2006).…”
Section: Twist1 Is a Target Of Hif-2a Eh Gort Et Almentioning
confidence: 99%
“…By comparison, enhancers of type II genes, such as rhomboid (Fig. 1C), contain highaffinity Dl-binding sites that are bound and activated by the lower levels of Dl that are present in the ventral neuroectoderm (Ip et al, 1992a). Recent computational analysis of a large set of Dl-responsive enhancers from the genomes of D. melanogaster and related species has confirmed that Dl affinity is a major determinant of the expression domains of Dl target genes (Papatsenko and Levine, 2005).…”
Section: Binding-site Affinitymentioning
confidence: 99%
“…7). Prior to esg, rho transcription is activated within the neuroectoderm anlage by Dorsal and is repressed within the mesoderm anlage by sna and twi (Ip et al 1992). Consequently, rho transcript and protein form gradients with their highest point at the boundary between the anlagen for the mesoderm and neuroectoderm (Bier et al 1990;Sturtevant et al 1994).…”
Section: Der-dependent Repression Determines Three Dorsoventral Domaimentioning
confidence: 99%